Bank loan prediction using machine learning - Mahottam, Parthosarothi; Anika, Antara Raida; Jahan, Dilshad; Lazika, Tanzina Afrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.